1993
DOI: 10.1095/biolreprod48.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Rat Uterine Estrogen Receptor Messenger Ribonucleic Acid Levels during Estrogen- and Progesterone-Induced Estrogen Receptor Depletion and Subsequent Replenishment1

Abstract: The overall objectives of this study were to determine whether the rapid decrease in estrogen receptor (ER) binding in the rat uterus after an injection of estradiol and subsequent recovery of ER levels was accompanied by similar changes in ER mRNA levels. Furthermore, the effect of progesterone administered under conditions known to decrease ER binding, in the rat uterus, on ER mRNA levels was also investigated. Ovariectomy for 14 days brought about a 3-fold increase in rat uterine ER mRNA levels, and these e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 54 publications
6
32
0
Order By: Relevance
“…4 C and D). The latter finding is consistent with previous reports (25,37). Uterine ER␣ levels were remarkably low in ovariectomized females on the Purina 5001 diet (Fig.…”
Section: Commercial Diets Alter Estrogen-responsive Gene Expression Isupporting
confidence: 93%
See 3 more Smart Citations
“…4 C and D). The latter finding is consistent with previous reports (25,37). Uterine ER␣ levels were remarkably low in ovariectomized females on the Purina 5001 diet (Fig.…”
Section: Commercial Diets Alter Estrogen-responsive Gene Expression Isupporting
confidence: 93%
“…These changes are similar in nature to those previously observed for native estrogen (7,(25)(26)(27)(28)(29)(30).…”
Section: Commercial Diets Alter Estrogen-responsive Gene Expression Isupporting
confidence: 87%
See 2 more Smart Citations
“…Furthermore, the apparent decrease in the total number of measurable binding sites after a hormone challenge in rat uteri is due to degradation of the protein [20,39]. This "processing" found in the regulatory action of E2 on its receptor was also reported in the same specie by other authors [3,13,33], but no data as such has been reported for sheep. The heterologous down-regulation observed also in PR uterine expression after E2 treatment in lambs [22] was unforeseen, and no mechanism of action for this has yet been proposed.…”
Section: Introductionmentioning
confidence: 70%